2019
DOI: 10.1186/s12711-019-0448-8
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of loci associated with mastitis resistance in two French dairy sheep breeds

Abstract: Background The identification of loci associated with resistance to mastitis or of the causative mutations may be helpful in breeding programs for dairy sheep as it is for cattle worldwide. Seven genomic regions that control milk somatic cell counts, an indirect indicator of udder infection, have already been identified in sheep (Spanish Churra, French Lacaune and Italian Sardinian–Lacaune backcross populations). In this study, we used a 960 custom-designed ovine single nucleotide polymorphism (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The development of genomic methods and tools for applications to sheep and the sequencing of the sheep genome [29] have greatly contributed in those efforts [13,30]. In a recent study, Oget et al [31] have confirmed the QTL regions associated with mastitis resistance in sheep of that breed.…”
Section: Discussionmentioning
confidence: 99%
“…The development of genomic methods and tools for applications to sheep and the sequencing of the sheep genome [29] have greatly contributed in those efforts [13,30]. In a recent study, Oget et al [31] have confirmed the QTL regions associated with mastitis resistance in sheep of that breed.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of 48 SNPs from 11 parasite-resistance genes located on 8 chromosome was chosen based on previous genome-wide association studies (GWAS) and marker-assisted selection studies (Carracelas et al 2022 ; Oget et al 2019 ; Archibald et al 2010 ) across the sheep genome (Table 1 ). The SNP data for Ovis were obtained from the NCBI’s Single Nucleotide Polymorphism Database (dbSNP http://www.ncbi.nlm.nih.gov ) or Ensembl ( http://www.ensembl.org ).…”
Section: Methodsmentioning
confidence: 99%
“…Since 2007, when the sheep genome was first sequenced, the development of low- and high-density ovine single nucleotide polymorphisms (SNP) chips [ 13 ] has allowed genome-wide association studies to reveal the genetic background of several diseases, including mastitis susceptibility in sheep [ 14 , 15 , 16 , 17 ]. These studies have highlighted several genome regions and some candidate genes, some of which are immune- and body growth-related, distributed on different chromosomes [ 16 , 17 , 18 , 19 ]. Despite this challenge in sheep, genome-wide association studies for mastitis have remained limited [ 3 ].…”
Section: Introductionmentioning
confidence: 99%